Designing a Model for Integrating Social Capital with Innovative Knowledge Management in Gaining Competitive Advantage and Development of the Country's Banks (Case Study: Sepah Bank Branches in Tabriz) - Rasouli Dizaji, Mohammad; Alavi Matin, Yaghoub; Fakhimi Azar, Sirous (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: Achieving a competitive advantage in the banking industry, which has transformed itself through the employment of unpredictable approaches, is both more difficult and more crucial. Therefore, the present research aimed to provide a model for integrating social capital with innovative knowledge management in gaining competitive advantage and developing the country's banks.Methodology: This study was conducted using a mixed (qualitative and quantitative) approach. The qualitative part was carried out through interviews with 15 managers and deputies of Sepah Bank branches in Tabriz and university professors specializing in innovative knowledge management and social capital, using grounded theory method. The quantitative part involves structural equations.Findings: The results from the interpretive structural modeling method for the components of social capital and knowledge management showed that tangible and cognitive dimensions, knowledge gathering, and knowledge dissemination have the highest impact, with the responsiveness component having the most significant influence in integrating the variables of social capital with knowledge management. Furthermore, the results indicated that, except for the impact of organizational culture on the empowerment of human resources with a path coefficient of 0.062 and a t-value of 1.535, which is less than 1.96 and not significant, all path coefficients are significant.Conclusion: The findings demonstrated that components such as tangible and cognitive dimensions, knowledge gathering, and knowledge dissemination at the first level and in the dependent region have the highest susceptibility, and the responsiveness components, which are in the independent region, have the highest impact in the integration of investment variables with knowledge management.